Analysis for Spatio-temporal Variation Characteristics of Extreme Precipitation in Wanquan River Basin - XIAO Jing; ZHANG Lu; LIN Youwen (Renmin Zhujiang)
Based on the long-sequence precipitation data of 22 rainfall stations,this paper selects eight extreme precipitation indexes to analyze the temporal evolution and spatial distribution of extreme precipitation in Wanquan River Basin by linear trend method,moving average,MK test and moving t-test.The results show that:①The spatial distribution of the annual mean values of the eight indexes in the north source (except Sihe station) and the middle and lower reaches of the Wanquan River Basin is similar,with relatively small fluctuation;while that in the south source shows great difference,with great fluctuation in the whole.②The extreme precipitation index increases slightly,indicating that the long-term variation trend is still uncertain.The long-term variation trend of the south source,north source and middle and lower reaches is differentiated.③Except for CWD,the seven indexes such as PRCPTOT in the basin have similar interdecadal rules,with obvious interdecadal changes and significant fluctuations after the 21st century.The interdecadal variation law of CWD is obvious,with large fluctuations.④The abrupt year of extreme precipitation index is different,for which the PRCPTOT is similar to Rx1day and R99PTOT,while other indexes are different.